Adaptive Fuzzy Modified Fixed-Time Fault-Tolerant Control on SE(3) for Coupled Spacecraft. (11th January 2021) - Mei, Yafei; Liao, Ying; Gong, Kejie; Luo, Da
Abstract : This paper aims to solve the control problem of coupled spacecraft tracking maneuver in the case of actuator faults, inertia parametric uncertainties, and external disturbances. Firstly, the spacecraft attitude and position coupling kinematics and dynamics model are established on the Lie group SE(3), and the coupled relative motion tracking error model is derived by exponential coordinates. Then, considering the actuator faults, an adaptive fuzzy scheme is proposed to estimate the lumped disturbances in real time, and a novel modified fixed-time terminal sliding mode fault-tolerant control law is developed to deal with the actuator faults and compensate the lumped disturbances. Next, the Lyapunov method is used to prove the stability and convergence of the system. Finally, the proposed controller can achieve fast and high-precision fault-tolerant control goals, and its effectiveness and feasibility are verified by numerical simulation.